STUDI KOMPARATIF USAHATANI PADI DAERAH HULU DAN HILIR DI DAERAH ISTIMEWA YOGYAKARTA - Intan Adhitya Rosmasari (FP AGRI 16 UMY 017, 2016)
THE COMPARATIVE STUDY OF RICE FARMING UPSTREAM AND DOWNSTREAM AREAS AT DAERAH ISTIMEWA YOGYAKARTA. This research aims to know the factors that influence to the production of rice and to knowing the differences in cost, revenue and profits of rice farming at upstream area and downstream area. This research uses simple random sampling with the numbers of respondents are the sixty farmer. The data were analyzed based of Cobb-Douglas production function and significancy differencent test. The results shows that factors of rice production which have influence are seed, fertilizer, land, and labor. Amount of rice production is increase in dry season and when it planted in upstream. Production of rice is decrease when rice planted in personal field. Cost, revenue dan profits of farming in the upstream and downstream area there is no difference.